Balance Pro, Atrazine, Autumn Super, Corvus, Sencor, Authority, and Banvel for Preemergence Kochia Control in Fallow - R. Currie; P. Geier (Kansas Agricultural Experiment Station Research Reports, 2017)
A study was initiated near Garden City, KS, in 2016 comparing kochia control of several herbicide treatments and their time of application in fallow. Spring applications of five tank mixes containing the active ingredient isoxaflutole provided greater than 92% control of kochia. Fall applications of similar tank mixes provided from 78 to 84% control. Tank mixes of atrazine and dicamba applied in the spring provided only 89% control.
Keywords: Application timing; early preemergence